Toward World Smart Government Rank - Achmad Nurmandi; Muhammad Younus (Jurnal Studi Pemerintahan, 2023)
Smart government is growing concept in government affairs and public administration today. The objective of this study is to explore smart government concept and make the world rank of smart government. This study used official world e-government and government data to defined component of smart government: Economic Growth, Policy Making, Citizen Engagement, Accountability, Interoperability, Key Enablers Innovation, Smart Service and Government Effectiveness.